Pengaruh Kredit Usaha Mikro Kecil dan Menengah (UMKM) dan Non Performing Loan (NPL) Bank Terhadap Gross Domestic Product (GDP) Indonesia - FreeztikA, Adelia Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this paper is to understand the impact of credit for UMKM and Bankâ€™s NPL to GDP in Indonesia. The study using 4 Commercial Bank which is include on BUKU 4 criteria over 2009-2016. In testing the hypothesis using statistical analysis by using multiple linear regression analysis for panel data. The results showed that the independent variables (DUMKM, KUMKM and NPL) of dependent (GDP) simultaneously and partially had a significant effect. Some of the 3 independent variables studied are only DUMKM variables that giveÂ influence in different directions. The UMKM Debtor (DUMKM) has a significant negative effect on GDP, which means that the increasing number of UMKM debtors will reduce the level of GDP, that happen because there are still obstacles that faces by the business unit in accessing banking financial services. So that, the UMKM credit in Indonesia is dominated by increasing the amount of credit owned by the old UMKM debtors. While the credit distribution of UMKM in Indonesia has not been able to provide easy access for prospective new debtors to access credit services in the banking sector.Kata kunci: GDP, NPL, Credit UMKM